SOSIAL-EKOLOGIS DALAM PEMBENTUKAN ENTITAS AGRIBISNIS KEMITRAAN DI TENGAH STRUKTUR SOSIAL KEMASYARAKATAN HETEROGEN - Herda Sabriyah Dara Kospa; Fachrurrozie Sjarkowi; Maryanah Hamzah (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
The scarcity of land in establishing agro industry causes the need of productive agribusiness partnership. The aim of this study are to: (1) identify social stratifications and social differenciations as determinant to establish agribusiness partnership entity, (2) describe social ecology characteristics as determinant to establish agribusiness partnership entity, (3) compare pre-plasma income and post-plasma expectation income. The research was conducted in Bandar Jaya and Umpam Villages Lengkiti Sub District of OKU Induk, South Sumatra Province. The purposive sampling method was used of which the farmers of yearly crop were chosen. The result of the social structure analysis showed that from the average income, education level and culture acceptance, the farmers would be responsive to the partnership. Subsequently, the analysis of socio-ecological characteristics of both villages indicated that the farmer’s of both villages would be more responsive to the partnership. The present value of revenues in both village lower than palm oil revenue expectation of partnership with PT AP. The results of this study indicated that Ho hypothesis is accepted, which means the farmers' income of pre-plasma (slab) in both villages less than the income of farmers expectations of post-plasma (oil palm), so that the partnership would be easily established. Keywords : Sosio-ecology; Agribusiness Partnership; Sosio-culture